SEARCH OF THE Na IN THE REGION OF THE SUBLIMATION OF THE NEAR-SUN DUST - Delone, A. B.; Divlekeev, M. I.; Suchanov, E. A.; Gulyaev, R. A.; Yakunina, G. V.; Porfir’eva, G. A. (Одеські астрономічні публікації, 2017)
An evaluation of the Na number in the sublimation zone of the near-Sun interplanetary dust, based on a comparison with the intensity of the radiation of the Na in the Earth atmosphere, has been obtained. The abundance of the Na in the column along the line of sight is less than 2 x 108atom cm-2. This result is compared with the values, determined on the base of the brightness of the zodiacal light, F-corona and by direct measurements of the dust density with space experiments.